Determining the Strategy & Techniques for Restoration of Healthy Aqua-ecosystem from Toxic Super Eutrophic Water Body - Peimin Pu; Jiangping Pu (Current Advances in Geography, Environment and Earth Sciences Vol. 6, 2022)
There are complex river-lake systems in the Taihu Lake catchment with total water surface area of 6174.7 km2, and population density of 1079/km2, including Taihu Lake water surface area of 2338 km2. The water systems in this catchment have healthy aqua-ecosystems during long history. However, the waters have been polluted with various levels. We should transform the pollutants by Physic Ecological Engineering (PEEN) into mainly bio-resources for use and form healthy water agriculture (HWA) and Bio-Environmental Enterprise (BEE) from local water segments step by step to whole catchment. As an example, we performed engineering in an “acute toxicity for higher organisms” and over standards for many heavy metal elements segment, where there were no any living plants and macro organisms in the water body and in sediments. The objective is how can we remediate this kind river-let segments in an as small as possible space/time scale into healthy aqua-ecosystem with clear water and abound plants and higher organisms output? The main strategy and techniques are: 1) soft-wall technique for controlling mass exchange between waters with different quality; 2) floating/suspending eco-island technique by using which can mosaic culture any plant which can be cultured in water; 3) immobilized nitrogen cycle bacteria (INCB) technique; 4) electronic pulse technique and photosensitization technique for tattering esters and other big-molecule organic chemicals; 5) mist spray facility technique for improving dissolved oxygen in deep water layers; 6) technique for buffering and suppressing H2S release from water; 7) the floating islands may connect on net system with about 1/3 portion of surface with cultured plant to the total water surface area, where might sustainable restore submerged plants. These technologies might be use for purifying various waters into raw water standard of drinking water.